Interactive system for placement and coordination of overcurrent protective devices - Campitelli, Eduardo M. [UNESP]; Da Silva, Luis G.W. [UNESP]; Pereira, Rodrigo A.F. [UNESP]; Mantovani, José R.S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2006)
In this paper, an expert and interactive system for developing protection system for overhead and radial distribution feeders is proposed. In this system the protective devices can be allocated through heuristic and an optimized way. In the latter one, the placement problem is modeled as a mixed integer non-linear programming, which is solved by genetic algorithm (GA). Using information stored in a database as well as a knowledge base, the computational system is able to obtain excellent conditions of selectivity and coordination for improving the feeder reliability indices. Tests for assessment of the algorithm efficiency were carried out using a real-life 660-nodes feeder. © 2006 IEEE.
Keywords: Combinatorial Optimization; Distribution Networks; Protection Design; Reliability; Algorithm efficiency; Computational system; Distribution network; Interactive system; Knowledge base; Mixed-integer nonlinear programming; Overcurrent protective devices; Placement problems; Protection systems; Protective devices; Radial distribution feeders; Reliability Index; Combinatorial optimization; Feeding; Genetic algorithms; Integer programming; Knowledge based systems; Nonlinear programming; Optimization; Overcurrent protection